PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK VIVA KOSMETIK PADA GENERASI Z - Ayu Karisma Febri Nadilawati; Christiawan Hendratmoko (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze and test the influence of Brand Image, Product Quality, and Price on the Purchase Decision of Viva Cosmetics products among Generation Z. Viva Cosmetics is a legendary brand that remains relevant and faces intense competition in the Indonesian skincare market. The research employs a quantitative approach, where primary data was collected through questionnaires distributed to respondents from the Generation Z demographic. The collected data was then analyzed using the multiple linear regression analysis method. The results show that Product Quality and Price have a significant and positive effect on purchase decisions. Conversely, Brand Image does not have a significant influence on Generation Z's purchase decision. This finding indicates that Generation Z consumers tend to prioritize functional factors such as Product Quality and Price over mere brand perception when making their purchasing choices.